2017
DOI: 10.1039/c7dt00043j
|View full text |Cite
|
Sign up to set email alerts
|

Combining imaging and anticancer properties with new heterobimetallic Pt(ii)/M(i) (M = Re, 99mTc) complexes

Abstract: In this article, we report on the development of new metal-based anticancer agents with imaging, chemotherapeutic and photosensitizing properties. Hence, a new heterobimetallic complex (Pt-LQ-Re) was prepared by connecting a non-conventional trans-chlorido Pt(ii) complex to a photoactive Re tricarbonyl unit (LQ-Re), which can be replaced by Tc to allow for in vivo imaging. We describe the photophysical and biological properties of the new complexes, in the dark and upon light irradiation (DNA interaction, cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Meanwhile, Quental et al (2017) designed a heterobimetallic complex consisting of a Re(I) tricarbonyl core and a platinum-iminedipyridyl group. Addition of platinum into the Re(I) complex (complex 7 ) was found to be capable of improving the toxicity of Re(I) by three folds towards HeLa cell lines (IC 50 from 42.8 µM to 13.5 µM, upon 10 min light irradiation at 350 nm and 2.58 J cm −2 ), achieving a similar photo-index value (PI) to that of the Photofrin (PI: average of 5) [ 35 , 102 , 103 ]. This suggests the potential for improving Re(I)’s phototoxicity via attachment of a Pt(II) cytotoxic complex.…”
Section: Phototoxic Effect Of Rhenium(i) Tricarbonyl Complexesmentioning
confidence: 99%
“…Meanwhile, Quental et al (2017) designed a heterobimetallic complex consisting of a Re(I) tricarbonyl core and a platinum-iminedipyridyl group. Addition of platinum into the Re(I) complex (complex 7 ) was found to be capable of improving the toxicity of Re(I) by three folds towards HeLa cell lines (IC 50 from 42.8 µM to 13.5 µM, upon 10 min light irradiation at 350 nm and 2.58 J cm −2 ), achieving a similar photo-index value (PI) to that of the Photofrin (PI: average of 5) [ 35 , 102 , 103 ]. This suggests the potential for improving Re(I)’s phototoxicity via attachment of a Pt(II) cytotoxic complex.…”
Section: Phototoxic Effect Of Rhenium(i) Tricarbonyl Complexesmentioning
confidence: 99%
“…Within the design of novel metallodrugs, the use of activation therapies such as the use of UVA light offers a wide fan of possibilities for metallic complexes such as activation of reactivity [8], change in conformation [9], heterobimetallic complexes with PDT ligands [10] and singlet oxygen producing complexes [11]. Photochemical studies on a selected number of trans iodido complexes initially showed that irradiation induces a faster reaction with CT DNA and a higher amount of Pt bound to DNA.…”
Section: Introductionmentioning
confidence: 99%
“…[6] The reconsideration of these iodido derivatives have shown a great impact in the field, and the trend and behavior of these complexes is being reevaluated. [7] Within the design of novel metallodrugs, the use of activation therapies such as the use of UVA light offers a wide fan of possibilities for metallic complexes such as activation of reactivity [8], change in conformation [9], heterobimetallic complexes with PDT ligands [10] and singlet oxygen producing complexes. [11] Photochemical studies on a selected number of trans iodido complexes initially showed that irradiation induces a faster reaction with CT DNA and a higher amount of Pt bound to DNA.…”
Section: Introductionmentioning
confidence: 99%